EPIDEMIOLOGICAL AND CLINICAL ASPECTS OF RETINOBLASTOMA IN DEVELOPING COUNTRY (World Journal of Current Medical and Pharmaceutical Research, 2023)
Introduction: Retinoblastoma is the most common intraocular tumor in child. Treatment depend on stadification and classification of retinoblastoma. The aim of this study was to describe epidemiological and clinical aspects of retinoblastoma in Madagascar.Method: We report in this retrospective study 44 cases found during 5 years, from January 2015 to December 2019. We have collected information about epidemiological and clinical aspect, delay of diagnosis. Classification of retinoblastoma was done with Reese Ellsworth classification and International Classification of Intra-ocular Retinoblastoma (ICRB). Data was collected with excel software and analysis was done with R-studio 4.2.2 software. The quantitative variables were expressed as an average and the qualitative variables as a proportion and percentage.Result: We had collected 44 cases. The incidence was 8.8 cases per year. Sex ratio was 1.3. Mean age was 40 months. Exophthalmos was found in 35% (n=12) of cases. Leukocoria was found in 24% (n=11) children. The delay time before diagnosis was 13 months. In 97.7% of cases, the retinoblastoma was unilateral. Intraocular form was found in 23 patients (52.3%). Among intraocular form 13 patients (57%) presented with grade E, including one patient with meningeal extension 9 patients (39%) with grade D, 1 patient (4%) in grade B. Extra ocular form was found in 21 patients (47.7%) : 17 (77%) had orbital invasion (stage III), 4 (23%) were metastatic (stage IV).Conclusion: Diagnosis of retinoblastoma was made in advanced stage. Most of patients had extraocular form. Prognosis was worse in Madagascar. Making diagnosis early is necessary to prevent loss of life.